The effect of media violence on the verbal aggressive behaviours of Malaysian Chinese independent secondary school students / Tan Yun Hoong, Paul GnanaSelvam Pakirnathan and Irene Law Hong Ling - Hoong, Tan Yun; Pakirnathan, Paul Gnanaselvam; Hong Ling, Irene Law (2020)
With the rising ownership of mobile phones and access to social media, school teachers have noted and reported on the increase in secondary school students' use of verbal aggressive behaviours at school compared to the past. Therefore, this study aimed to identify the effect of media violence on the verbal aggressive behaviours of male and female Chinese independent secondary school students in Malaysia. In this quantitative study, 380 male and female Malaysian secondary school students enrolled in Forms Three to Five were selected through simple random sampling method. A self-administered questionnaire was distributed through a survey form. The Free Time Questionnaire (Gunderson, 2006), Content-Based Media Exposure Scale (Den Hamer, 2017), and the Verbal Aggressive Scale (Infante& Wigley,1986) were used to collect data. The data were then analysed using the SPSS- 23. The results showed that the most popular media used among Malaysian secondary school students were videos and computer games. The results also showed that media violence significantly affected the verbal aggressive behaviours of Malaysian Chinese independent secondary school students. However, there was no significant difference between male and female students in indulging in verbally aggressive behaviours. Thus, the results of this study are significant for parents, educators and school administrators to be aware on the types of media violence that could indirectly stimulate students to committing verbally aggressive behaviours which in turn lead to other negative socio-communicative implications.